2015
DOI: 10.1111/1440-1630.12182
|View full text |Cite
|
Sign up to set email alerts
|

The Cognistat (neurobehavioural cognitive status exam): Administering the full test in stroke patients for optimal results

Abstract: Our findings confirm that occupational therapists should administer the full Cognistat to stroke patients rather than the original screen-metric approach. A two-factor structure was also supported in our results, suggesting that occupational therapists' scoring practices should reflect this finding and use the differentiated score out of 10 rather than a global sum. However, additional research is necessary to consider the clinical and theoretical significance of the Cognistats' subscale clustering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The researchers indicated that the Cognistat can be used a primary cognitive screen for the TBI population (Doninger et al, 2006). Rice, Campbell, Friedman, Speechley, and Teasell (2015) analyzed the psychometric properties of the Cognistat (2011) to determine if the screen-metric design was a reliable method to administer the Cognistat. Additionally, the researchers assessed the construct validity of the Cognistat within the CVA population.…”
Section: Cognitive Impairments In Abimentioning
confidence: 99%
See 4 more Smart Citations
“…The researchers indicated that the Cognistat can be used a primary cognitive screen for the TBI population (Doninger et al, 2006). Rice, Campbell, Friedman, Speechley, and Teasell (2015) analyzed the psychometric properties of the Cognistat (2011) to determine if the screen-metric design was a reliable method to administer the Cognistat. Additionally, the researchers assessed the construct validity of the Cognistat within the CVA population.…”
Section: Cognitive Impairments In Abimentioning
confidence: 99%
“…The results showed inconsistency between five out of ten subscales. Some individuals who passed the screen items of the Cognistat failed the metric portion (Rice et al, 2015). The researchers suggested these findings indicated low sensitivity, and accuracy in detecting possible cognitive impairments using the screen-metric approach of the Cognistat in individuals with CVA (Rice et al, 2015).…”
Section: Cognitive Impairments In Abimentioning
confidence: 99%
See 3 more Smart Citations